Sperm cryopreservation of sex-reversed rainbow trout (Oncorhynchus mykiss): incorporation of amino acids and anti-oxidants to the extender media to improve the anti-oxidant system - Kocabas, Filiz Kutluyer; Kocabas, Mehmet; Benzer, Fulya; Erisir, Mine (Urmia Univ, 2026)
Anti-oxidants are vital for protecting sperm and can mitigate the negative effects associated with cryopreservation. This study was conducted to evaluate the protective effects of adding anti-oxidants (vitamins and amino acids) to extender in sex-reversed rainbow trout (Oncorhynchus mykiss) sperm. The collected sperm was diluted at the ratio of 1 : 5 by the extenders supplemented with different anti-oxidants including 1.00 mM of ascorbic acid and L-tryptophan, 2.00 mM of cysteine and alpha tocopherol, and their combination. After dilution, the semen was aspirated into 0.50 mL straws, and the straws were placed on the tray, frozen for 10 min, and plunged into liquid nitrogen. Straws were thawed in a 30.00 & ring;C water bath for 15 sec. The Sperm Class Analyzer System was used to evaluate sperm kinematics. The activity of anti-oxidant enzymes and lipid peroxidation were determined as oxidative stress indices. Our data indicated that the incorporation of anti-oxidants and amino acids increased sperm motility duration. The elevated activity of glutathione peroxidase, superoxide dismutase, and catalase in post-thaw samples indicates that the anti-oxidant system in sex-reversed rainbow trout sperm likely plays a crucial role in protecting membrane compounds from oxidation. In conclusion, the combination of 1.00 mM L-tryptophan and ascorbic acid to the extender media caused a prolonging effect in sperm motility after thawing and they have the potential to serve as effective agents for improving sperm cryosurvival. (c) 2026 Urmia University. All rights reserved.
Keywords: Amino acid; Anti-oxidant; Rainbow trout; Sex-reversed; Sperm